Experimental and analytical evaluation of rubberized polymer concrete. (30th November 2017) - Jafari, Khashayar; Toufigh, Vahab
Highlights: Destructive tests and non-destructive methods were conducted on rubberized PC. The mechanical properties of rubberized PC were determined. The feasibility of adding waste tire rubber to PC was investigated. The optimum mixture of rubberized PC was obtained by using Taguchi and ANOVA. The most effective factor in the compressive and tensile strengths was chipped rubber. Abstract: Polymer concrete (PC) has been widely used for quick repairing of concrete pavement and structures in recent years. This paper studies the mechanical behavior of the rubberized polymer concrete. Crumb and chipped rubber were used to replace fine and coarse aggregates in PC, respectively. A complete series of destructive tests including impact test, compression and splitting tensile tests and non-destructive methods including ultrasonic test, digital signal processing, electrical conductivity, and microstructure analysis was performed to demonstrate the various potential applications of the rubberized PC. X-ray diffraction (XRD) also provided information regarding the chemical composition and crystal structure of three different epoxy resin ratios. The results indicated that the rubberized PC reduced the workability and increased the porosity and air content of the mixture; however, reduced the cost and density, and improved ductility. Scanning electron microscope was used to analyze the interface between aggregates and adhesive materials. The correlation between the compressive strength and ultrasonic pulse velocity was determined and proposed for the rubberized PC. PC containing crumb rubber had a lower pulse velocity and higher damping properties than that of chipped rubber. Further, the Taguchi method was used to determine the optimum conditions for mechanical properties of the rubberized PC and ANOVA was then utilized to evaluate the level of influence and existence of interaction parameters. Based on this investigation, the rubberized PC can be an appropriate candidate for repair and rehabilitation applications.